The Effect of COVID-19 Pandemic on Arrival Time of Acute Stroke Patients in The Emergency Department of Abdoel Wahab Sjahranie Hospital - Hutahaean, Yetty Octavia; Kharisma, Benny Hary; Adam, Muhammad Fadlan (Jurnal Kesehatan Pasak Bumi Kalimantan, 2025)
Introduction: The COVID-19 pandemic is thought to have an effect on the arrival of acute stroke patients to the emergency department (ED). This study aims to determine the effect of the COVID-19 pandemic on the arrival time of acute stroke patients to the ED since the time of onset. Methods: This study is an observational cross-sectional analytical study with purposive sampling in acute stroke patients who came to the ED of Abdoel Wahab Sjahranie Hospital Samarinda whose stroke onset time was known. Data were taken from medical records from the period before the COVID-19 pandemic in March 2019-April 2020 and the period during the COVID-19 pandemic in March 2020-April 2021. Data analysis used the Chi-Square test. Results: The difference in the number of acute stroke patients hospitalized before and after the COVID-19 pandemic was obtained p = 0.000. The difference between the arrival time of acute stroke patients to the ED before and after the COVID-19 pandemic was obtained p = 0.678. The relationship between age, health insurance ownership, address, and consciousness status with the time of arrival at the ED during the COVID-19 pandemic was obtained sequentially p = 0.641, p = 0.668, p = 0.679, p = 0.679, and p = 0.018. Conclusion: There was a decrease in the number of acute stroke patients coming to the ED of Abdoel Wahab Sjahranie Hospital Samarinda during the COVID-19 pandemic. There was a significant relationship between consciousness status and the time of arrival at the ED during the COVID-19 pandemic, indicating that acute stroke patients tend to go to the ED more quickly when there is a decrease in consciousness.